2020
DOI: 10.3390/polym12040883
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Salicylate Donors in Enhancement of Productivity and Isotacticity of Ziegler–Natta Catalyzed Propylene Polymerization

Abstract: Roles of internal salicylate donors (SID) in enhancing activity and stereoselectivity of Ziegler–Natta catalyzed propylene (PP) polymerization were examined using DFT calculations. Five salicylate donors were studied. The chelate mode is the preferred adsorption mode. The linear relationship (R2 = 0.96) between calculated adsorption energies (Eads) of five SIDs and the experimental PP activities was observed. Thus, the SID with the strongest adsorption energy will provide the highest activity in agreement with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…As a result, we can conclude that the M-X distance is critical in the design of Ti (O, X)-FI-based catalysts. Furthermore, our calculations revealed that all of the product structures had a strong ß-agostic interaction, as evidenced by the elongated C R -H ß bond distance (1.13-1.15 Å) compared to the standard C-H bond distance of 1.10 Å [64].…”
Section: Tablementioning
confidence: 72%
“…As a result, we can conclude that the M-X distance is critical in the design of Ti (O, X)-FI-based catalysts. Furthermore, our calculations revealed that all of the product structures had a strong ß-agostic interaction, as evidenced by the elongated C R -H ß bond distance (1.13-1.15 Å) compared to the standard C-H bond distance of 1.10 Å [64].…”
Section: Tablementioning
confidence: 72%